Consulted ethical problems of clinical nursing practice: perspective of faculty members in Japan - Mari Tsuruwaka (BMC, 2017)
Abstract Background There are several studies that have targeted student nurses, but few have clarified the details pertaining to the specific ethical problems in clinical practice with the viewpoint of the nursing faculty. This study was to investigate the ethical problems in clinical practice reported by student nurses to Japanese nursing faculty members for the purpose of improving ethics education in clinical practice. Method The subjects comprised 705 nursing faculty members (we sent three questionnaires to one university) who managed clinical practice education at 235 Japanese nursing universities. We performed a simple tabulation of the four items shown in the study design. 1) the details of student nurse consultations regarding ethics in clinical practice (involving the students themselves, nurses, care workers, clinical instructors, and nursing faculty members); 2) the methods of ethics education in clinical practice; 3) the difficulties experienced by the nursing faculty members who received the consultations; and 4) the relationship between clinical practice and lectures on ethics. Furthermore, the analysis was based on the idea of ethical principles, respect for persons, beneficence, and justice. Results The response rate was 28% (198 questionnaires). The nursing faculty members were consulted for various problems by student nurses. The details of these consultations were characterized by the principles of respect for patient by nurses, the principles of benevolence by faculty and clinical instructors, and the principle of justice pertaining to evaluations. The results indicate that there is an awareness among the nursing faculty regarding the necessity of some sort of ethics education at clinical settings. Moreover, based on the nature of the contents of the consultations regarding the hospital and staff, it was evident that the nursing faculty struggled in providing responses. More than half of subjects exhibited an awareness of the relationship between the classroom lectures on ethics and clinical practice. Conclusion The results suggest the need for analyzing the ethical viewpoints of student nurses, prior learning, and collaboration with related courses as part of ethics education in clinical practice.